Experiences of sexual orientation in youth: reflections from cultural-historical psychology - da Silva, Rômulo Lopes [UNESP]; de Souza, Vera Lucia Trevisan (Universidade Federal do Paraná, 2024)
The experience of sexuality during youth has sparked political and social debates in Brazilian society, shaping distinct forms of subjective constitution and social inclusion for young gay individuals. This study aimed to reflect on the role that experiences related to non-heterosexual orientation play in the life trajectories of young gay people. The data was collected through semi-structured online interviews with two young individuals who self-identify as gay. These reflections stem from an intervention research project by Historical-Cultural Psychology and gender and sexuality studies. The interviews were analyzed using Nuclei of Meaning approach, which highlights the historical and social processes of meaning-making about being a young gay person. The reflections reveal the tensions and conflicts present in the social life of gay youth in the current historical context, where the experiences of the two young individuals illuminate the social roles they assume amidst situations of individualization, conservatism, and diminishing collectivity.
Vivências da orientação sexual na juventude: reflexões a partir da Psicologia Histórico-Cultural
Keywords: historical-cultural psychology; homosexuality; sexuality; young